2015
DOI: 10.1093/deafed/env025
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Language, Hearing Status, and Visual-Spatial Skills

Abstract: It is frequently assumed that deaf individuals have superior visual-spatial abilities relative to hearing peers and thus, in educational settings, they are often considered visual learners. There is some empirical evidence to support the former assumption, although it is inconsistent, and apparently none to support the latter. Three experiments examined visual-spatial and related cognitive abilities among deaf individuals who varied in their preferred language modality and use of cochlear implants (CIs) and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
57
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 79 publications
(96 reference statements)
12
57
3
2
Order By: Relevance
“…Finally, any or all of the above reasons might result in deaf learners having delays, deficits, or simply differences in social maturity-related executive functioning (EF) relative to hearing peers. This possibility would be consistent with emerging evidence with regard to links between EF and performance among deaf learners in other domains (e.g., Kronenberger, Colson, Henning, & Pisoni, 2014;Marschark, Spencer, et al, 2015). These alternatives are considered below as background to a study that was aimed at better understanding possible relations among social maturity and EF among deaf learners.…”
supporting
confidence: 53%
See 4 more Smart Citations
“…Finally, any or all of the above reasons might result in deaf learners having delays, deficits, or simply differences in social maturity-related executive functioning (EF) relative to hearing peers. This possibility would be consistent with emerging evidence with regard to links between EF and performance among deaf learners in other domains (e.g., Kronenberger, Colson, Henning, & Pisoni, 2014;Marschark, Spencer, et al, 2015). These alternatives are considered below as background to a study that was aimed at better understanding possible relations among social maturity and EF among deaf learners.…”
supporting
confidence: 53%
“…Marschark, Spencer et al (2015) also found a significant relationship between EF and spoken language among deaf college students who used CIs and relied primarily on spoken language, whereas deaf students who did not use CIs and relied primarily on sign language demonstrated a strong association of EF with sign language ability as well as with age of sign language acquisition. Importantly, better scores on measures of both communication and EF have been associated with more prosocial behavior, fewer behavior problems, and fewer problems in peer relationships (Hintermair, 2013).…”
Section: Executive Function Language and Social Functioning Among Dmentioning
confidence: 81%
See 3 more Smart Citations